Accelerating Social Enterprises’ Growth through Business Innovations: The Case of GK Enchanted Farm - Galang, Maricel Correa (ASEAN Multidisciplinary Research Journal, 2022)
Social enterprises are community change agents that contribute significantly to the economy, yet they confront obstacles such as scaling-up and receiving insufficient assistance. An evidence-based case study concentrating on the case of Gawad Kalinga Enchanted Farm, its residents, and the social entrepreneurs in the area was conducted to determine the support needed by social enterprises in accelerating their growth through business innovations. The qualitative research method was employed in this study because it allowed the researcher to acquire a better understanding of how innovation contributes to each social enterprise’s dimension and why each is important to success. The findings reveal that social enterprise’s value proposition, key resources, key activities, key partners, and cost structure are the features that set it apart from other businesses. As a result, social entrepreneurs should employ innovative approaches to continuously improve their products and processes, with a focus on the aforementioned aspects that are crucial to attaining their objectives. To aid the establishment and expansion of social enterprises, business support services and infrastructure, as well as a network of social entrepreneurs who can offer greater options for impact, could be offered. The support of a social enterprise’s partner institution, whether public or private, and how the social entrepreneur uses innovative methods to improve their value proposition, key resources, key activities, key partners, and cost structure are all important factors in accelerating social enterprise’s growth. As a result, an innovative social enterprise model with a support system is determined to be critical in achieving its goal.